VD_FINDINFO HC / 2012 / 123 vom 22. Februar 2012 - VD Tribunal cantonal (2012)
EXPULSION DE LOCATAIRE, PROCÉDURE SOMMAIRE | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 257 al. 1 let. a CPC (CH), 257 CPC (CH)